Perbandingan Performans Kambing Lokal yang Diberikan Pakan Fermentasi Kulit Ari Biji - Muhammad Ichsan Hidayat (Mitra Sains, 2020)
The research aims to understand the impact of feeding & rationing non fermented food and fermentation of cacao’s placenta on development and physiology of the local goats. The research was done in three months starting in Februari and ended in April 2019 located a CV. Prima BREED’s farm in Tondo Mantikulore Palu Central Sulawesi. This research uses factorial experiment which is designed with RAL (Rancangan Acak Lengkap) 2x5 which is repeated three time, on which first factor of Cacao’s Placenta consists of two treatments which are Unprocessed Cacao’s Placenta and Processed Cacao’s Placenta The second factor consist of five levels of concentrasion feedings. Observed parameters are weight increase, consumption of dried ration ration, usage efficiency. Interaction result shows thet the feedings of cacao’s placenta + feeding levels has insignificant influence on development of local goats. The feeding of cacao’s placenta shows significant influence on the increase of body weight 49,69 (g/head/day) and ration efficiency 0,12 (g/headr/day). Fermented ration gives best development on the development of local goats.